PENGARUH PENGELOLAAN KELAS TERHADAP PRESTASI BELAJAR MATA PELAJARAN FIQIH SISWA SMA MAARIF BUMI RESTU - Dedi Jumarwan (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research is to find out influence of parents attention againt student achievement through student motivation. This type of research was ex-post facto using quantitative approach. Instruments were used are scale and documentation. The research subject were Arabic Language Subject SMA Ma’arif Bumi Restu District drawn by proportional random sampling. The research was analyzed by path analysis. The results show that parents attention has positve effect on student achievement through student motivation with regression line equation Y=44,02+0,05X+0,42Z, Fcount > Ftable (88,31 > 3,92) and Tcount > Ttable (4,00 > 1,98). The influence of parents' attention againt student achievement through student motivation by 60% with contribution of parents’ attention to student motivation by 0,35 and contribution of student motivation to student achievement by 0,42.